Activities of Social Studies Teachers in Non-governmental Organizations and Perception of Volunteering - Faiz, Melike (Bilge Akademi, 2020)
Volunteering can be stated as activities performed for the benefit of the society regardless of the interests of the people. Such activities are of great importance for the strengthening of the social structure. In this study, the activities of social studies teachers in non-governmental organizations and the perception of volunteering were tried to be determined. In this context, the research was carried out in the phenomenology pattern, which is one of the qualitative research methods. The study group of the study consisted of 38 social studies teachers determined by purposeful sampling method. In the study, the data were collected by structured interview form and analyzed by descriptive analysis method. The results of the research: In the definition of volunteering in the study, the most repeated result is the benefit of society, benevolence, and favorable income without waiting for a financial response. It was concluded that volunteering increases solidarity and empathy and improves unity-togetherness and solidarity. In the study, the reasons for the low rate of volunteerism in Turkey unconsciousness, educational shortcoming is that prejudice and politics intertwined. It was concluded that the most needed volunteering activities should be in the fields of education, environment, children and health.
Keywords: 4. Education; 10. No inequality